Personalized medicine: paradigm shift in ALK positive non-small cell lung cancer: a case report - Barreira, JV (2023)
Background: Since the identification of multiple therapeutic targets, as is the case of anaplastic lymphoma kinase (ALK) translocation, the paradigm of treating patients with non-small cell lung cancer (NSCLC) has improved. In order to guarantee the possibility of longer survival outcomes with a better quality of life we must invest in the determination, in suitable time, of the consensual biomarkers and in the availability of the best treatments to our patients. Case presentation: We present a case of a caucasian male in his fifth decade of life, non-smoker, who highlights the complex journey of ALK-positive patients. This particular case, demonstrates the efficacy and tolerability of the new ALK target therapies, allowing our patients to maintain their routines without compromising the effectiveness of the therapy. Conclusion: Focusing on the reality of ALK positive patients and the impact that this therapy has on the daily lives of our patients, we can contribute to the awareness of this specific pathology.